Intra-Industry Trading Factors and Patterns in ASEAN-5 Region - Muryani, Muryani; Pratiwi, Anisa Dyan (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2018)
The large expansion of trade in the form of Intra-Industry Trade (IIT) in ASEAN is driving large volumes and variety of traded goods and is changing patterns of trade across members. This paper examines the factors affecting the level of IIT for ASEAN-5 countries (Indonesia, Malaysia, Philippines, Singapore, and Thailand) in the period of 2004-2014. IIT is measured with Grubel-Lloyd index covering ten different one-digit SITC categories. The result indicates a large Intra-Industry Trade among ASEAN countries and across most manufacturing sectors. IIT Index is employed as a dependent variable, and four variables are used as independent variables: 1) different GDP per capita, 2) foreign direct investment (FDI), 3) trade openness, and 4) distance. Different GDP per capita and trade openness have a positive effect on IIT. FDI does not affect IIT, and distance has a negative effect on IIT across intra-ASEAN trade. Keywords: International Trade, Intra-Industry Trade, Grubel-Lloyd, Panel Data Analysis